(untitled) (Journal of Mathematical Study, 2016)
In this paper, the existence and stability results for ground state solutions of an m-coupled nonlinear Schrödinger system i∂∂ tu_j+∂²∂x²u_j+^m_i=1b_ij|u_i|^p|u_j|^p-2u_j=0, are established, where 2 ≤ m, 2≤p